Parental Verbal Abuse and Its Association with Emotional Development and Anxiety in Adolescents - Krisnana, Ilya; Rachmawati, Praba Diyan; Anggari, Anita Firmanti Kartika; Soares, Domingos (Universitas Pendidikan Indonesia, 2025)
Introduction: Continuous verbal abuse from parents towards children can cause emotional disorders and hinder children development, both physical and psychological development. Objective: This study aims to explain the relationship between verbal abuse by parent with the emotional development and level of anxiety among adolescents. Methods: The research sampling technique used a simple random sampling, and 282 respondents were obtained as research sample. The independent variable in this study was verbal abuse by parents on adolescents’ perspective, while the dependent variable were emotional development and anxiety level among adolescents. The instruments used the verbal abuse questionnaire, Strength and Difficulties Questionnaire (SDQ), and the Depression, Anxiety, and Stress Scale-42 questionnaire (DASS-42). The data was analyzed by using the Spearman rank correlation test with a significance value of p 0.05. Results: The result showed that there is a relationship between verbal abuse by parent with emotional development (p = .001) and anxiety levels (p = .001) among adolescents. Conclusions: This study reveals a significant link between parental verbal abuse and maladaptive emotional development and increased anxiety in adolescents. The findings highlight the need for early interventions and educational programs promoting positive parenting to prevent verbal abuse and support healthy emotional growth. Positive parenting and healthy parent-child interactions can help ensure that children develop normal emotional regulation and anxiety levels.